Descriptivism without quotation - Franken, Dirk (Topoi, 2020)
Current descriptivist accounts of proper names entail two claims: (i) that the expressions we know as different proper names are the bearers of different meanings and (ii) that the descriptions corresponding to these meanings contain quotations of the expressions whose meanings they are taken to be. While (ii) is the source of a number of intractable problems, descriptivists feel committed to it because it is the only available option to adhere to (i), which they use to take as a matter of course. In the present paper I will bring up for discussion a, to my knowledge, new descriptivist account, inter-nominal descriptivism, which avoids the commitment to (ii) by rejecting (i). According to this account, all tokens of the expressions known as different proper names express the same descriptive mode of presentation and this descriptive mode of presentation is akin to the character of an indexical. I will try to show that, contrary to first appearance, this idea can be developed in a consistent and plausible manner.
Published online: 30 March 2018
Gesehen am 07.04.2021